Volume 5: Materials Technology; CFD and VIV 2008
DOI: 10.1115/omae2008-57149
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Fatigue of Simulated C-Mn Steel HAZs in Sour Produced Fluids

Abstract: Steel Catenary Risers are subjected to both fatigue loading (from waves and tides) and corrosive environments (internal and external). The financial benefit of using C-Mn steels for SCRs is significant, therefore there is a need to establish the limitations of the material. These limitations are likely to be controlled by the HAZ, as HAZ microstructures are typically more susceptible than parent steel to cracking during exposure to a sour environment, especially if they have high hardness. Samples of API 5L X6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Another important effect of sour environments on FCGR is the cycle frequency; usually it is found that with decreasing frequency the FCGR increases and reaches a plateau. 2,[8][9] The role of hydrogen diffusion through the fracture process zone as the rate-limiting step in FCGR of steels under various conditions has been developed to account for the observations of FCGR. The decrease in FCGR with increasing frequency has been attributed to insufficient time for hydrogen diffusion through the fracture process zone at higher frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Another important effect of sour environments on FCGR is the cycle frequency; usually it is found that with decreasing frequency the FCGR increases and reaches a plateau. 2,[8][9] The role of hydrogen diffusion through the fracture process zone as the rate-limiting step in FCGR of steels under various conditions has been developed to account for the observations of FCGR. The decrease in FCGR with increasing frequency has been attributed to insufficient time for hydrogen diffusion through the fracture process zone at higher frequencies.…”
Section: Introductionmentioning
confidence: 99%